If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96a + 4b = 4 Solving 96a + 4b = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. 96a + 4b + -4b = 4 + -4b Combine like terms: 4b + -4b = 0 96a + 0 = 4 + -4b 96a = 4 + -4b Divide each side by '96'. a = 0.04166666667 + -0.04166666667b Simplifying a = 0.04166666667 + -0.04166666667b
| 5(-9+3y)-2y=7 | | 14=6y+y | | (x-5)(2x+8)= | | 3(6+5y)=-2(-5+4y) | | 216x-162=18(12x-9) | | 31.2p=65.1 | | (3x-24)+2x=2x | | 6(1/2u-2/3) | | 1/2x^2-6=0 | | 7x-3(3x+17)=-37 | | 2x-2+x=x-24 | | Cot/cos=CDC | | -9x-3y=7 | | 10x+26x-10=9(4x+10) | | 3(4-6y)+7=-1 | | M/9--213=231 | | 12.1=p+2.3 | | X-(156-X)=78 | | 3x-24+2x=2x | | 38x+85=38x+78 | | x2=49/81 | | 5x+4(-3x-10)=103 | | 3/4(2x–8) | | X/-1/6=6/7 | | x^2+4x-8y+12=0 | | -5(f-929)=85 | | P+2p+3p+2=2 | | 7x+23x-4=6(5x+9) | | 18(w+25)=468 | | 4x-2(1+2x)=6 | | 3.4w=9.7 | | 34x+3y=12 |